2008
DOI: 10.1016/j.ygeno.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression analysis of iodide-treated rat thyroid follicular cell line PCCl3

Abstract: The inhibitory effect of supraphysiological iodide concentrations on thyroid hormone synthesis (Wolff-Chaikoff effect) and on thyrocyte proliferation is largely known as iodine autoregulation. However, the molecular mechanisms by which iodide modulates thyroid function remain unclear. In this paper, we analyze the transcriptome profile of the rat follicular cell lineage PCCl3 under untreated and treated conditions with 10(-3) M sodium iodide (NaI). Serial analysis of gene expression (SAGE) revealed 84 transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
0
34
1
6
Order By: Relevance
“…Highest overexpression (5.77-fold) was observed with the Tpo (thyroid peroxidase) gene. This contrasts with findings from previous studies reporting either no effect of iodide treatment on Tpo expression (23,39,40) or even downregulation of its expression (41,42) in thyroid cells or lines. The reasons for this discrepancy are unclear but may be due to the different protocols used.…”
Section: Kolypetri and Carayanniotiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Highest overexpression (5.77-fold) was observed with the Tpo (thyroid peroxidase) gene. This contrasts with findings from previous studies reporting either no effect of iodide treatment on Tpo expression (23,39,40) or even downregulation of its expression (41,42) in thyroid cells or lines. The reasons for this discrepancy are unclear but may be due to the different protocols used.…”
Section: Kolypetri and Carayanniotiscontrasting
confidence: 99%
“…Interestingly, increased expression of Gpx2, Txn1, but not Gpx4 has been previously reported in the rat PCCL3 thyroid cells after iodide treatment in vitro (40,43). Other identified genes were as follows.…”
Section: Kolypetri and Carayanniotismentioning
confidence: 61%
“…However, in rats previously treated with MMI, which is known to block TPO activity (15,31,42) and, as a consequence, the production of iodolipids, the effect of NaI excess on NIS mRNA abundance and polyadenylation was preserved, which strengthens our hypothesis that iodide itself is the key element for eliciting the effects reported. This assumption is also reinforced by the studies performed by Leoni et al (24), which showed that PCCl3 cells, under iodide and MMI treatment, presented a reduction of NIS gene expression, indicating that this anion per se is capable of regulating the NIS expression.…”
Section: Discussionmentioning
confidence: 69%
“…It can also be expected that the efficiency of the NIS mRNA translation would be impaired in this condition, as pointed out before (30). Even though these findings point to a posttranscriptional control of NIS mRNA expression by iodide, they do not exclude the possibility that longer periods of iodide exposure could also affect the NIS gene transcription rate, as already described (13,14,24).…”
Section: Discussionmentioning
confidence: 73%
“…evidence that an acute high dose of iodine blocks iodide organification by inhibiting the activity of TPo and reduces the expression of niS at both the mrna and protein levels has been presented (16,21). a previous study shows that methimazole, an inhibitor of TPo activity, blocks iodine organification and abolishes an acute Wolff-Chaikoff effect (15).…”
Section: Discussionmentioning
confidence: 99%